﻿Halamphora taxa in Hungarian soda pans and shallow soda lakes detected via metabarcoding and microscopic analyses - Éva Ács; Tibor Bíró; Emil Boros; Péter Dobosy; Mónika Duleba; Angéla Földi; Keve T. Kiss; Zlatko Levkov; Péter Orgoványi; Orsolya Pálné Szén; Zsuzsa Trábert; Edit Vadkerti; et al. (Metabarcoding and Metagenomics, 2023)
The research presented investigates whether DNA-based metabarcoding can replace the morphology-based identification of diatom taxa in the ecological status assessments of aquatic habitats. When comparing data obtained with microscopy and metabarcoding, significant deviations have been noticed. One of the main reasons includes the incompleteness of the reference database used for taxonomic annotation of sequences. The database library should be complemented with species inhabiting unique habitats and having specific environmental requirements representing environmental endpoints for genetic diversification. Soda pans and soda lakes are examples of an extreme habitat with the loss of sodic character as the main threat; thus, accurate identification of species and exact information on their salinity tolerance is essential for adequate ecological status assessment. In the present study, by using microscopy and metabarcoding, we investigated taxa of the genus Halamphora that are common in soda pans and soda lakes. We detected six species of which Halamphora dominici and H. veneta occurred frequently and often in high abundance (it was often dominant having relative abundance higher than 5%). Analyses of DNA data confirmed the separation of the two species; as a result, the reference database library has been supplemented with sequences of H. dominici. Furthermore, we have confirmed that this species, which is a significant indicator of sodic character, shows a positive correlation with salinity.